A Study O The Policies And Practices Of Teacher Education In Malaysia Towards Producing Quality Pre-Service Teachers. - Jamil, Hazri; Abd Razak, Nordin; Ahmad, Mohammad Zohir; Issa, Jinan Hatem (2010)
The teaching profession is vital for the achievement of Malaysian educational aims of enhancing education quality and developing the human capital of the nation. The Malaysian government has worked to improve the quality of teachers and recruit highly-qualified people to the teaching profession by improving remuneration and opportunities for promotion.